1970
DOI: 10.2134/agronj1970.00021962006200060039x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Soil‐grown Roots in a Rhizotron1

Abstract: Measurements were made of both shoot and root growth on a corn (Zea mays L.) and a tomato (Lycopersicon esculentum Mill.) plant in a rhizotron. Root intensity at the transparent panel was estimated by two methods. It increased during the growing season for both species, but was always greater for corn. Estimates of root density and total root length were three times greater for corn than for tomato at the end of the growing season. Side walls and glass panels showed no concentrating effect on root growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
2

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 4 publications
2
42
0
2
Order By: Relevance
“…Under moist conditions it is not the average concentration of inorganic N in the soil solution which is likely to limit uptake, but the proportion of roots which have access to it (Burns, 1980). Tomato plants utilize only a small fraction of the available soil inorganic N because of their low rooting density (Jackson and Bloom, 1990;Taylor et al, 1970). Determinant cultivars of processing tomatoes develop smaller root systems under field conditions than semideterminant fresh market tomatoes (Widders and Lorenz, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Under moist conditions it is not the average concentration of inorganic N in the soil solution which is likely to limit uptake, but the proportion of roots which have access to it (Burns, 1980). Tomato plants utilize only a small fraction of the available soil inorganic N because of their low rooting density (Jackson and Bloom, 1990;Taylor et al, 1970). Determinant cultivars of processing tomatoes develop smaller root systems under field conditions than semideterminant fresh market tomatoes (Widders and Lorenz, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Root-length density was calculated by dividing the length of fine roots observed in each video frame by the soil volume observed (182 mm# frame areaia depth of field of 2.5 mm) and converting to mm −$ . The 2.5-mm depth of field, midway between previously used values of 2 mm (Taylor et al, 1970) and3 mm (Itoh, 1985), was chosen because it resulted in average minirhizotron root-biomass densities which matched those determined by root coring. To determine rootbiomass density (g m −$ ), root-length density was divided by specific root lengths of 11.72 m g −" for 0-1-mm fine roots and 2.31 m g −" for 1-2-mm fine roots, which were empirically determined from root cores next to the minirhizotron tubes.…”
Section:  mentioning
confidence: 99%
“…Similar assumptions were made also and may not be valid either. It was assumed that the visible distance, was' 3 mm in this case, that is I.S times the value postulated by TAYLOR et al (1970). As the root concentration can be 3 times higher in the 2 mm soil layer immediately behind the mini-rhizotron window (BOHM, 1979), BOHM et al (1977) concluded that the mini-rhizotron should not be used for rooting density studies.…”
mentioning
confidence: 95%
“…TAYLOR et al (1970) measured the root length on the window and attempted to calculate the rooting density in bulk soil assuming that all roots within 2 mm of the observation panel were visible. It was also assumed that the rooting density in the soil near the observation panel was not high compared with that of the bulk soil.…”
mentioning
confidence: 99%